Telemedicine in cardiology - Agnieszka Kujawska; Daria Bieniek; Marcin Kożuchowski; Ewa Dzienniak; Mateusz Domeracki (Kazimierz Wielki University, 2019)
Introduction Telemedicine is becoming regularly used in rural part of some of developed countries. Moreover, it could be applied to improve diagnosis and emergency care in adults as well as in neonatal care. Material and methods Articles in the EBSCO database have been analyzed using keywords: telemedicine, cardiology. The available literature is subjectively selected. Then, the newest version of every paper was searched for. Results Results of researches with applications of telemedicine in cardiology in emergency, chronic conditions. Moreover, potential costs and benefits were described. Conclusions Telemedicine could be useful for patients, their families, clinicians and regional healthcare systems. The rapidly changing healthcare climate includes an increasing focus on cost reduction, quality improvement and results, patient-centered care and technology solutions, all of which are well served by the optimal use of telemedicine.